2014
DOI: 10.1039/c4dt00184b
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar behavior of MWW materials in aldol condensation of furfural and acetone

Abstract: MWW family of different structural types (MCM-22, MCM-49, MCM-56 and MCM-36) was used as catalysts for aldol condensation of furfural and acetone studied in a batch reactor at 100 °C, autogenous pressure and a reaction time of 0-4 h. To establish a relation between physico-chemical and catalytic properties of microporous materials, the samples were characterized by XRD, SEM, N2 adsorption, FTIR and TGA. It was found that the acidic solids possessed appreciable activity in the reaction and resulted in the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 76 publications
(106 reference statements)
2
38
0
1
Order By: Relevance
“…306 Other authors have explored other catalysts including N-substituted Na-Y; 316 Co-Al spinels; 317,318 mixed oxides such as Mg-Al, [319][320][321] Ca-Zr, 322 WO 3 -ZrO 2 , 323 other MgO-ZrO 2 species, 322,[324][325][326][327] supported Mg-Zr oxides on graphite 328 or MgO/Na-Y, 329 dolomites 330 , chitosan, 331 and zeolites. 332,333 For prospective industrial applications of these catalysts, it is of paramount importance to address the stability of the solids in the reaction medium along with the activity. Most of the studies compiled in Table 8 refer to the deposition of heavy species as the main cause of deactivation.…”
Section: Claisen-schmidt Condensation and Derived Biofuelsmentioning
confidence: 99%
“…306 Other authors have explored other catalysts including N-substituted Na-Y; 316 Co-Al spinels; 317,318 mixed oxides such as Mg-Al, [319][320][321] Ca-Zr, 322 WO 3 -ZrO 2 , 323 other MgO-ZrO 2 species, 322,[324][325][326][327] supported Mg-Zr oxides on graphite 328 or MgO/Na-Y, 329 dolomites 330 , chitosan, 331 and zeolites. 332,333 For prospective industrial applications of these catalysts, it is of paramount importance to address the stability of the solids in the reaction medium along with the activity. Most of the studies compiled in Table 8 refer to the deposition of heavy species as the main cause of deactivation.…”
Section: Claisen-schmidt Condensation and Derived Biofuelsmentioning
confidence: 99%
“…Owing to their enhanced external surface areas compared to conventional zeolites, two-dimensional zeolites are considered more appropriate catalysts for aldol condensation reactions involving bulky compounds, as they occur in primary pyrolysis vapours from biomass. Kikhtyanin et al 380 explored a variety of layered zeolites belonging to the MWW family in aldol condensation of furfural and acetone. A batch reactor operating at 100 1C under autogenous pressure was employed and their activity was compared with that of Beta zeolites.…”
Section: Hierarchical Zeolites In Catalytic Pyrolysismentioning
confidence: 99%
“…Rodrigues et al 299 and Kikhtyanin et al 300 studied the formation of coke in the comparative studies of MCM-22, pillared MCM-36 and delaminated ITQ-2. In both studies it was found that the hierarchization of the structure prevented excessive coke formation and the catalyst life-time was substantially increased.…”
Section: Layered Zeolitesmentioning
confidence: 99%